Methodology and Reporting of Mobile Heath and Smartphone Application Studies for Schizophrenia. Issue 3 (May 2017) - Torous, John; Firth, Joseph; Mueller, Nora; Onnela, J. P.; Baker, Justin T.
Abstract : Abstract: The increasing prevalence of mobile devices among patients of all demographic groups has the potential to transform the ways we diagnose, monitor, treat, and study mental illness. As new tools and technologies emerge, clinicians and researchers are confronted with an increasing array of options both for clinical assessment, through digital capture of the essential behavioral elements of a condition, and for intervention, through formalized treatments, coaching, and other technology-assisted means of patient communication. And yet, as with any new set of tools for the assessment or treatment of a medical condition, establishing and adhering to reporting guidelines—that is, what works and under what conditions—is an essential component of the translational research process. Here, using the recently published World Health Organization mHealth Evaluation, Reporting and Assessment guidelines for evaluating mobile health applications, we review the methodological strengths and weaknesses of existing studies on smartphones and wearables for schizophrenia. While growing evidence supports the feasibility of using mobile tools in severe mental illness, most studies to date failed to adequately report accessibility, interoperability, costs, scalability, replicability, data security, usability testing, or compliance with national guidelines or regulatory statutes. Future research efforts addressing these specific gaps in the literature will help to advance our understanding and to realize the clinical potential of these new tools of psychiatry.